Purification and structural characterization of three novel anti-adhesive peptides against Helicobacter pylori from corn gluten meal - Guanlong Li; Xiaolan Liu; Zhengfei Miao; Xiqun Zheng (Journal of Functional Foods, 2024)
More than 50% of the world population is infected with Helicobacter pylori (H. pylori). Potential anti-adhesive peptides from corn protein hydrolysate were developed using in vitro methodologies to prevent Helicobacter pylori infection. To obtain anti-adhesive peptides against Helicobacter pylori, corn gluten meal (CGM) was hydrolyzed by neutrase, and the hydrolysate (CPHN) was purified by using Superdex peptide gel filtration, Q anion exchange and Mono Q anion exchange. Then, sequences of peptides were identified by Nano-LC-MS/MS, and the structural and functional properties of the identified peptides were characterized. Three novel peptides Pro-Tyr-Ala-Glu-Tyr (PYAEY, PY5), Ile-Ile-Pro-Gln-Cys-Ser (IIPQCS, II6) and Thr-Ile-Ile-Pro-Gln (TIIPQ, TI5) were identified, respectively. PY5 exhibited the best anti-adhesive activity among the three novel peptides, and its anti-adhesive activity was 40.75 ± 0.72% at 4 mg/mL. Meanwhile, PY5 also possessed significant 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity and excellent 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging capacity, with IC50 values of 1.650 ± 0.184 and 0.007 ± 0.001 mg/mL, respectively, suggesting that PY5 could alleviate stomach damage induced by Helicobacter pylori infection. In addition, molecular docking and dot blot results showed that PY5 could also conjugate with the Helicobacter pylori adhesins, SabA and BabA, through hydrophobic interactions and hydrogen bond inhibiting Helicobacter pylori adhesion. These results indicate that three novel peptides from corn protein hydrolysate have potential anti-adhesive and antioxidant effects and could serve as functional foods or drugs to prevent Helicobacter pylori infection.